Can Cryptocurrencies Be Treated as a Safe Haven? - Parzonka, Julia (Czy kryptowaluty mogą być traktowane jako bezpieczna przystań?, 2023)
In late February 2022, the escalation of the Eastern European conflict triggered a global stock sell-off. Over the course of the day, the MOEX plummeted by 33%, WIG20 recorded an 11% drop and the VIX fear index surged. Instinctively, investors began to relocate the capital to traditional safe assets. This article aimed to verify whether cryptocurrencies can be treated by investors as a financial safe haven. The article presents the post-war-outbreak behavior of major cryptocurrencies in comparison with selected stock market indices and traditional safe havens. Three hypotheses were tested: whether cryptocurrencies can be a safe haven during crises, whether certain types of cryptocurrencies are outperforming others at protecting capital, and how the time horizon affects their properties. Despite the uncertainty in the scientific world, the article proves that cryptocurrencies do not meet the criteria for safe havens. The analysis and modeling were based on the DCC-GARCH approach.
Parzonka, J. (2023). Can Cryptocurrencies Be Treated as a Safe Haven? W: M. Swacha-Lech, I. Dittmann (Eds.), Finanse (pp. 99-111). Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu.
Keywords: safe haven; cryptocurrency; dynamic correlation; DCC-GARCH; financial market; bezpieczna przystań; kryptowaluty; dynamiczna korelacja; rynek finansowy